Keterlibatan Peran Orang Tua, Masyarakat, Dan Pemerintah Terhadap Penelantaran Anak Berkebutuhan Khusus - Hana Mufidah; Insani Nurul Qolbi; Khairunnisa Kamilah; Safina Salsabila Ramadhani Nur; Siti Hamidah (Universitas Maritim AMNI Semarang, 2023)
Children with special needs are children who experience disorders or obstacles in their development and academics. This limitation has a negative impact due to the misunderstanding of the acceptance of parents and society for children with special needs. So that more and more children with special needs are neglected by their parents, not only by letting children live alone, but not fulfilling basic needs is a form of child neglect. This study aims to describe the impact and factors causing neglect of children with special needs as well as the role of the family, community and government in fulfilling the rights of children with special needs, especially in the right to a decent life and the right to education. Data were collected through interviews and systematic review. The results show that neglect of children with special needs has a negative impact on their development and academic aspects. One of the main factors causing children with special needs to be neglected is the parents' lack of acceptance of their children's condition, which gives the view that the limitations of children with special needs are seen as weaknesses that cannot be fixed. In this case, the support and role of the family, community and government hold an important contribution in eliminating the negative stigma that arises and develops in society as well as in fulfilling the rights of children with special needs themselves. Parents' acceptance of the child's condition, changes in the mindset of people who view children with special needs as unfit to be in society, and the role of the government in formulating laws for children with special needs, providing public facilities that suit the needs of children with special needs and providing inclusive schools are a unity that must be considered and run in tandem in order to create a decent life for children with special Needs.